The relationship of social media use in learning and academic performance among undergraduates in Faculty of Educational Studies, UPM - Muhamad, Ibrahim; Che Hassan, Norlizah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
There has been increasing use of Social Media among students across the world. Literature regards social media as websites and software that primarily allow users to ‘‘connect, communicate, and interact with each other’’. Therefore, research is needed to describe undergraduate students' experiences on using social media for learning. Previous studies have looked at the utilization of specific social media tools.. Each focused on a particular tool, such as the usage of blogs or podcasts. Other studies investigated just the role of frequently-used social media among university students. This research project will focus on undergraduate students' use of Facebook, YouTube and Twitter for learning and academic performance at the context of UPM. This paper has summarized about the problem statement, objective of study and theoretical framework. It has described and explained that forms at basis and direction of this study according to objective. Objectives of the study will establish the goals to be achieved at the end of the study. Then, several questions will develop based on the objectives of the study. The study will be beneficial to the undergraduates, teachers, universities and educators. Four theories have been explained and very related to the study, which include theories of Ecological Systems by Urie Bronfenbrenner, Greeno's (1997) by situated learning theory, social learning theory by Albert Bandura (1977) and Connectivism theoretical framework by Siemens (2005) and Downes (2005).